Minimal Central Series of a Nilpotent Product of Abelian Lie Algebras (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
We determine the structure of the lower central terms and the structure of the minimal central terms of the nilpotent product of free abelian Lie algebras of finite rank.